Analisis Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Pada Sektor Perusahaan Non-Keuangan - Yulia Kumoro, Merry Susanti (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study was to find out the effect of Dividend Payout Ratio (DPR), Current Ratio (CR), Return on Assets (ROA), Firm Size, Debt to Equity Ratio (DER), and Firm Growth on firm value of non-financial companies listed in Indonesia Stock Exchange period 2017-2019. The sampling method that used was purposive sampling with total sample were 85 data. Data processed by E-views 11. The result showed that debt to equity ratio had positive effect on firm value, while the other which is dividend payout ratio, current ratio, return on assets, firm size, and firm growth did not had effect on firm value. The implication of this study was the management team of the company needs to pay more attention to debt to equity ratio because this affect the firm value and investors found it attractive.